2010
DOI: 10.1089/ten.tea.2009.0230
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Receptor Signaling Is Not Involved in Osteogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: Platelet-derived growth factor (PDGF) receptor signaling plays an important role in the regulation of proliferation and migration of skeletal cells such as osteoblasts or mesenchymal stem cells (MSCs). However, involvement of these receptors in the process of osteoblastic differentiation of MSCs is still a matter of debate. The aim of our study was to examine the role of PDGF receptor signaling in osteogenic differentiation of human MSCs. For this purpose, we performed PDGF receptor stimulation as well as inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
2
25
1
Order By: Relevance
“…A similar effect on osteodifferentiation was previously described by Chevallier, Parsons and Prinse [17-19]; this effect can be related to the age of the platelet donors [20]. Other authors have cast doubts on the influence of platelet lysate on osteogenic differentiation [21-23]. Further experiments in this area are needed in order to utilize expanded hMSCs in therapeutic protocols for tendon healing because osteogenesis in tendons is undesirable and must be prevented.…”
Section: Discussionsupporting
confidence: 52%
“…A similar effect on osteodifferentiation was previously described by Chevallier, Parsons and Prinse [17-19]; this effect can be related to the age of the platelet donors [20]. Other authors have cast doubts on the influence of platelet lysate on osteogenic differentiation [21-23]. Further experiments in this area are needed in order to utilize expanded hMSCs in therapeutic protocols for tendon healing because osteogenesis in tendons is undesirable and must be prevented.…”
Section: Discussionsupporting
confidence: 52%
“…This response may be somewhat unique to ASCs, as previous studies have shown that PDGF signaling either has no effect or even an inhibitory effect on the osteogenic differentiation of bone marrowderived MSCs. [33][34][35][36][37] In vascular cultures, PDGF signaling had minimal effects on vascular network properties, with only low levels of exogenous PDGF-BB contributing to a slight increase in network density. PDGF signaling did, however, significantly affect pericyte coverage of the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] A number of studies have demonstrated that in vivo administration of exogenous PDGF-BB significantly enhances bone formation. [30][31][32] Yet, in vitro studies with MSCs have reported that while exogenous PDGF-BB induces greater proliferation, it has no effect on, [33][34][35] or may even be inhibitory to, 36,37 osteogenic differentiation. With regard to ASCs, it has been shown that during osteogenic differentiation, their expression of the PDGF receptor b (PDGFR-b) is upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…I t i s a l s o promoting malignant cell motility (Kumar et al, 2010) and it is implicated in osteoblastosteoclast interactions (Sanchez-Fernandez et al, 2008). When the PDGF/PDGFR signaling pathway is stimulated, the patients are presenting a worst prognosis (Hassan et al, 2011;Entz-Werlé et al, 2007b).…”
Section: The Osteoblastic Growth Factors and Their Receptors Which Amentioning
confidence: 99%